Patrimônio público: de todos ou de ninguém? Um estudo antropológico sobre intervenções ao patrimônio escolar - Machado, Gabriela Martins (2014)
Why do students produce marks on school walls, tables and cabinets? Were these purely violent demonstrations related to free riot and vandalism against the educational institution? The purpose of this study is to seek answers to these questions by finding alternative interpretations to common sense for the interventions done by goers of school public spaces. To do so, we performed ethnographic fieldwork with bias at the State Institute of Education Tiaraju, located in Sao Sepe / RS, where subsidies were extracted to demonstrate what kind of relationship the students have with the school environment, how these invisible links are externalized and materialized and for what reasons the school can be considered a local heritage.